Fraud in Rights and Contracts: A Review of Bankruptcy Case of Livent Inc. Based on Governance, Risk, and Compliance (GRC) Framework - Samuel Anindyo Widhoyoko (Binus Business Review, 2017)
This research discussed the accounting scandal in the perspective of governance, risk, and compliance using Governance, Risk, and Compliance (GRC) framework. The purpose of the research was to highlight earlybusiness fraud that usually initiated by the company in boosting up the revenue during the Initial public offering (IPO) processes. This research focused on a case showing how a business could make the wrong statement to the investors through real and lawful future contracts with unqualified audit opinion. Structurally, this research was done through the action research method in pointing out all the directors’ failures in their function to hold the fiduciary duty to exercise their responsibility. Based on the analysis, it is highlighted that directors in the aspect of (1) governance decisive, they fail to set proportional target, provide ethical value, and react positively to maintain the company sustainability; (2) compliance submissive, they do not submit the accounting standards throughundisclosed third-party agreement, misrepresentation of revenue recognition, and mistreatment of expense omission; (3) risk preventive, they fail to assess the risk occurs from legal aspect of conflict of interest, long-term contractual and engagement risks, and insufficient future cash flow.